2017
DOI: 10.1186/s13039-017-0315-7
|View full text |Cite
|
Sign up to set email alerts
|

Identification of mosaic and segmental aneuploidies by next-generation sequencing in preimplantation genetic screening can improve clinical outcomes compared to array-comparative genomic hybridization

Abstract: BackgroundChromosomal mosaicism is observed as the presence of both euploid and aneuploid cells in a particular blastocyst. Recent studies have reported that the implantation rate of mosaic embryo transfer is remarkably lower than the euploid embryos. The superior capability of next-generation sequencing (NGS) to detect chromosomal mosaicism in preimplantation genetic screening (PGS) remains controversial, and several data displayed similar implantation and pregnancy rates using NGS or array comparative genomi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
36
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(37 citation statements)
references
References 46 publications
1
36
0
Order By: Relevance
“…The authors suggested that NGS detects mosaicism and triploidy better than aCGH, and this improvement in detection might have a positive impact on the clinical outcomes by decreasing the incidence of miscarriage (Maxwell et al 2016). The superiority of NGS for the detection of mosaicism has been supported by another study where there were 6.7% in overall inconsistencies of mosaicism between two methods (Lai et al 2017), NGS detected those not identified by aCGH. On the other hand, settings with a customized analysis software with a high specificity of detection of mosaicism might nonetheless pose a potential risk of overdiagnosing euploid embryos as mosaic.…”
Section: Next-generation Sequencingmentioning
confidence: 81%
“…The authors suggested that NGS detects mosaicism and triploidy better than aCGH, and this improvement in detection might have a positive impact on the clinical outcomes by decreasing the incidence of miscarriage (Maxwell et al 2016). The superiority of NGS for the detection of mosaicism has been supported by another study where there were 6.7% in overall inconsistencies of mosaicism between two methods (Lai et al 2017), NGS detected those not identified by aCGH. On the other hand, settings with a customized analysis software with a high specificity of detection of mosaicism might nonetheless pose a potential risk of overdiagnosing euploid embryos as mosaic.…”
Section: Next-generation Sequencingmentioning
confidence: 81%
“…6 in [1]). In humans, about 1% of all pregnancies include some form of deviation from normal diploidy [25], and chromosomal deletions of embryonic malformations data revealed that about 11% of the genome has never been recovered in the haploid condition or any other copy number variation [26][27][28][29]. Although small deletions in human genomes are recognized as largely underestimated [30], segmental aneuploidies have been identified in oocytes, 10.4%, raising to 24.3% by three days of embryogenesis, and declining to 15.6% in preimplantation blastocysts [31].…”
Section: Introductionmentioning
confidence: 99%
“…At 5-15%, complex systems are required to handle the imputation and when >15%, the estimation will be strongly affected. Several explanations have been given for the occurrence of MVs and most of them involve the presence of artifacts, hybridization failures, and low-resolution on the microarray [8].…”
Section: Introductionmentioning
confidence: 99%